2023
DOI: 10.3390/ijms24021676
|View full text |Cite
|
Sign up to set email alerts
|

Paulownia Organs as Interesting New Sources of Bioactive Compounds

Abstract: Paulownia spp. is a genus of trees in the Paulowniaceae family. It is native to southeastern Asia (especially China), where it has been cultivated for decorative, cultural, and medicinal purposes for over 2000 years. Depending on taxonomic classification, there are 6 to 17 species of Paulownia; P. tomentosa, P. elongata, P. fortunei, and P. catalpifolia are considered the most popular. Nowadays, Paulownia trees are planted in Asia, Europe, North America, and Australia for commercial, medical, and decorative pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…An m 6 A modification is involved in regulating mRNA expression, translation efficiency, alternative splicing and mRNA degradation. The m 6 A transcriptome was sequenced for PaWB-diseased and PaWB-recovered (MMS-treated diseased, 16S rRNA gene-nested PCR-negative) P. fortunei plantlets grown in vitro [68]. The results indicated that MMS treatment lowered the m 6 A modification degree in PaWBrecovered paulownia, compared to diseased plantlets.…”
Section: Messenger Rna Modification (Epitranscriptome)mentioning
confidence: 99%
See 4 more Smart Citations
“…An m 6 A modification is involved in regulating mRNA expression, translation efficiency, alternative splicing and mRNA degradation. The m 6 A transcriptome was sequenced for PaWB-diseased and PaWB-recovered (MMS-treated diseased, 16S rRNA gene-nested PCR-negative) P. fortunei plantlets grown in vitro [68]. The results indicated that MMS treatment lowered the m 6 A modification degree in PaWBrecovered paulownia, compared to diseased plantlets.…”
Section: Messenger Rna Modification (Epitranscriptome)mentioning
confidence: 99%
“…The m 6 A transcriptome was sequenced for PaWB-diseased and PaWB-recovered (MMS-treated diseased, 16S rRNA gene-nested PCR-negative) P. fortunei plantlets grown in vitro [68]. The results indicated that MMS treatment lowered the m 6 A modification degree in PaWBrecovered paulownia, compared to diseased plantlets. When combined with RNA-seq data, 315 differentially methylated genes (DMGs) were screened from DEGs.…”
Section: Messenger Rna Modification (Epitranscriptome)mentioning
confidence: 99%
See 3 more Smart Citations